Changes in the Vaginal Microenvironment as Related to Frequency of Pessary Removal. Issue 2 (March 2018) - Fregosi, Nicole J.; Hobson, Deslyn T.G.; Kinman, Casey L.; Gaskins, Jeremy T.; Stewart, J. Ryan; Meriwether, Kate V.
Abstract : Objective: The aim of the study was to describe the effect of frequency of pessary removal on the vaginal microenvironment. Methods: We performed a secondary analysis of a multicenter randomized trial of hydroxyquinoline gel in women presenting for pessary fitting. Patients had vaginal secretions analyzed at baseline, 2 weeks, and 3 months. Patients were stratified by frequency of pessary removal at least once daily, at least once weekly, and less often than once weekly. These groups were compared for prevalence of Lactobacillus predominance (primary outcome), anaerobic predominance, Mobiluncus prominence, vaginal symptoms, and bacterial vaginosis by Nugent criteria, and correction for confounding variables was performed. Results: One hundred thirty-seven women were included in this analysis: 34 (25%) removed the pessary daily, 54 (39%) at least weekly, and 49 (36%) less often than once weekly. Women who removed the pessary less often than weekly were older ( P < 0.01), using more hormone therapy ( P = 0.03), and more likely to have bacterial vaginosis at baseline ( P < 0.01). At 2 weeks, the predominance of Lactobacillus in the group removing pessary daily was higher (41% daily vs 24% weekly vs 9% longer, P = 0.03) and this persisted after confounder correction ( P < 0.01). Women who removed their pessary less than weekly were more likely to have anaerobic predominance at 3 months ( P = 0.04). Conclusions: Women who remove their pessaries less often than once weekly have an increased prevalence of anaerobes at 3 months, but no difference in vaginal symptoms or pessary satisfaction. Abstract : Women who remove their pessaries less often than once weekly have an increased prevalence of anaerobic predominance and bacterial vaginosis in their vaginal microenvironment at 3 months after fitting, but no difference in pessary satisfaction or vaginal symptoms.